2022
DOI: 10.1186/s12889-022-14025-8
|View full text |Cite
|
Sign up to set email alerts
|

Transition to endemic: acceptance of additional COVID-19 vaccine doses among Canadian adults in a national cross-sectional survey

Abstract: Background Additional doses of COVID-19 vaccine have been proposed as solutions to waning immunity and decreased effectiveness of primary doses against infection with new SARS-CoV-2 variants. However, the effectiveness of additional vaccine doses relies on widespread population acceptance. We aimed to assess the acceptance of additional COVID-19 vaccine doses (third and annual doses) among Canadian adults and determine associated factors. Methods W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
11
2
Order By: Relevance
“…Our findings are similar with a cross-sectional survey study conducted in Europe, which indicated that 82.4% of participants from a German-speaking region were willing to receive annual vaccinations. However, the percentage from our study is higher than that of a survey study to examine Canadian adults’ willingness to accept annual vaccines, which indicated that 64.7% of the respondents reported the acceptance of an annual COVID-19 vaccine dose [ 13 ]. The high acceptance rate among Chinese-American participants in our study may suggest that the idea of making COVID-19 vaccination an annual routine is feasible and acceptable.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Our findings are similar with a cross-sectional survey study conducted in Europe, which indicated that 82.4% of participants from a German-speaking region were willing to receive annual vaccinations. However, the percentage from our study is higher than that of a survey study to examine Canadian adults’ willingness to accept annual vaccines, which indicated that 64.7% of the respondents reported the acceptance of an annual COVID-19 vaccine dose [ 13 ]. The high acceptance rate among Chinese-American participants in our study may suggest that the idea of making COVID-19 vaccination an annual routine is feasible and acceptable.…”
Section: Discussionmentioning
confidence: 65%
“…Future winter surges of COVID-19 have been predicted by five years of epidemiological models which suggest that COVID-19 is likely becoming another endemic respiratory virus that may require annual or intermittent booster immunization for the management and control of the pandemic due to the global mutations and the success of the authorized vaccine [ 11 , 12 ]. While the scientific evidence for annual vaccination is promising, this strategy needs population acceptance and public health vaccination promotion efforts [ 13 ]. It is critical to understand an individual’s intentions concerning potential annual COVID-19 vaccination and the factors associated with their vaccination decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is now a reality, and most Americans understand that COVID-19 is here to stay [ 1 ]. As mutations and natural selection continue to occur, new variants emerge and vaccines need to be continuously redeveloped [ 14 ] and adopted by the population [ 17 , 18 , 19 , 20 , 21 , 22 ]. In the U.S., the federal government has purchased 66 million doses of bivalent boosters that target BA.4 and BA.5 Omicron subvariants [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we likely need annual vaccine composition updates [ 18 ]. Surveys in Jordan show that less than 1 in 5 persons would take an annual booster [ 19 ], while about 2 in 3 Canadians [ 20 ] and more than 4 in 5 German-speaking adults would be willing [ 21 ]. Results in the U.S. are mixed, as surveys were conducted across sub-populations with different profiles [ 22 ].…”
Section: Introductionmentioning
confidence: 99%